SOLITON DEFORMATION OF INVERTED CATENOID - Kurmanbayev, D.; Yesmakhanova, K. (Academic Scientific Journal of Computer Science, 2021)
The minimal surface (see [1]) is determined using the Weierstrass representation in three-dimensional space. The solution of the Dirac equation [2] in terms of spinors coincides with the representations of this surface with conservation of isothermal coordinates. The equation represented through the Dirac operator, which is included in the Manakov’s L, A, B triple [3] as equivalent to the modified Veselov-Novikov equation (mVN) [4].